MEMBANGUN KEPERCAYAAN DIRI ANAK MELALUI PELATIHANPUBLIC SPEAKING GUNA PERSIAPKAN GENERASI BERKARAKTER - Unggul Priyadi (UII, 2013)
The success of education, especially formal education is determined by thesuccessful implementation of teaching and learning activities that is by empowering thestudents. Armed with confidence, every child could certainly develop into a humanberstimulus character. Children who are confident will be able to accept himself, readyto accept thechallenge in the sense of want to try something new even though awarethat the possibility of one must have and tend to be more successful in doing what hewants. While children who lack confidence will be someone who is pessimistic in theface of challenges, fearful and hesitant to express ideas, wavering in the choice and oftencomparing themselves to others. Since the development of personality, mental attitudeand Intellectual formed at an early age and the need for a gradual process, then thechild's confidence needs to be built from the outset. Quality early childhood is areflection of the quality of the nation to come. By using the method of public speakingtraining, public speaking and the gaming public speaking contest in the pack in a funlearning and in support of other facilities in the expected confidence of the students atSD Kemejing will increase. Thus students in elementary Kemejing can speak fluently,dare to ask, dare to declare: the question is also no need for coercion before finallywilling to step in front of the class so as to optimize in an effort to prepare the nextgeneration of character.